Norms of international law in the field of combating corruption crimes - Nikishkin A. V., Stepanov I. V., Pereniuk D. I. (Economics and management: realias and prospects, 2019)
The paper considers corruption as the most common disease of the state apparatus of countries around the world. Also possible ways for the organization of effective fight against crimes of corruption orientation and eradication of this problem by joint efforts of all world States and their law enforcement agencies are considered
Keywords: противодействие коррупции; международное сотрудничество; государственный аппарат; личная выгода; международная арена; опасное деяние; компенсация ущерба; мировое вычленение; the state apparatus; self-interest; international arena; anti-corruption; international cooperation; dangerous act; compensation of damages; the international isolation